The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jam.14587
|View full text |Cite
|
Sign up to set email alerts
|

Apple endophyte community is shaped by tissue type, cultivar and site and has members with biocontrol potential againstNeonectria ditissima

Abstract: Aims This research aimed to identify factors influencing endophyte community structure in apple shoots and the bioactivity of cultured representatives against the fungal pathogen Neonectria ditissima. Methods and Results The endophyte community in leaves and stems of the apple cultivars ‘Royal Gala’ and ‘Braeburn’ were analysed by a cultivation‐independent method (PCR‐DGGE) which showed that tissue type, cultivar and site were determinant factors, with the endophyte taxa in ‘Royal Gala’ more variable than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 80 publications
(100 reference statements)
2
24
0
Order By: Relevance
“…Plant organ type was the main factor influencing the composition and richness of endophytic fungi in P. colorata and indicated that it is an overriding factor in the formation of endophytic fungal communities in P. colorata tissues. Similar findings were reported in other studies where tissue type primarily influenced the diversity and community structure of endophytic fungi [34,37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Plant organ type was the main factor influencing the composition and richness of endophytic fungi in P. colorata and indicated that it is an overriding factor in the formation of endophytic fungal communities in P. colorata tissues. Similar findings were reported in other studies where tissue type primarily influenced the diversity and community structure of endophytic fungi [34,37].…”
Section: Discussionsupporting
confidence: 91%
“…The amplified PCR products were separated in 8% (w/v) polyacrylamide gel (acrylamide/bis solution, 37.5:1) with a linear gradient of 25-55% denaturant using a Cipher DGGE Electrophoresis system (CBS Scientific, Del Mar, CA, USA) [33]. Phoretix 1D Pro Gel Analysis (Totallab, Newcastle upon Tyne, UK) and Primer version 7 (Primer-E Ltd., Plymouth Marine Laboratory, Plymouth, UK) were used to analyze the endophytic fungal communities as previously described [34]. Each band in the DGGE gel was considered as one fungal taxon.…”
Section: Diversity Analysis Of the Endophytic Fungi In P Colorata Using Dggementioning
confidence: 99%
“…The extent of endophyte colonization in plants by endophytes was observed to be correlated to disease resistance [33]. Liu et al, [41] reported that the endophyte community-shaping in apple is being determined by the type of tissue, the sampling site, and cultivar, which in turn have a prominent impact on the number of potential antifungal biota strains present. The plant endosymbiosiomes have been widely used to isolate microflora with biocontrol ability [42] and the studies on such entities have revealed their abilities to contribute in conferring resistance to crops against various phytopathogens, including other substantial benefits on the host such as nutrient acquisition, enhanced growth, and improved resistance to heat, drought, and other stresses [43].…”
Section: Discussionmentioning
confidence: 99%
“…A culture-dependent analysis identified firmicutes of the genus Bacillus, Lysinibacillus, and Paenibacillus, and gammaproteobacteria of the genus Pseudomonas. There are some studies involving endophytes in reducing apple diseases, such as apple rot and European canker caused by Valsa mali and Neonectria ditissima, respectively, and the apple scab caused by Venturia inaequalis [11][12][13][14]. However, the ecological environment and cultivated varieties of apple-producing areas in Yunnan, China are different from those in northern China [2,15] and other apple-production areas in the world.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ecological environment and cultivated varieties of apple-producing areas in Yunnan, China are different from those in northern China [2,15] and other apple-production areas in the world. Different varieties and ecological environments are bound to breed different communities of endophytic bacteria [12,16]. The endophytic bacteria in Yunnan are bound to be more suitable for the ecological environment of Yunnan than endophytic bacteria from other places.…”
Section: Introductionmentioning
confidence: 99%